Nivel de conocimiento del tratamiento de tuberculosis entre el área de medicina privada y el área del MSP del cantón de Machala en el año 2010 - Gía C., César G. (2010)
Tuberculosis, once called consumtion is an infectious disease caused by several species of the genus Mycobacterium, all belonging to the Mycobacterium tuberculosis complex. The most important and representative, the cause of tuberculosis is Mycobacterium tuberculosis.